Video atlas of arthroscopic rotator cuff repair - Srikumaran, Uma (Thieme, 2021)
"Rotator cuff disorders are the most common cause of shoulder pain, accounting for up to 70% of cases. Tears are the most severe subtype, with a lifetime prevalence rate of more than 20%. The size, location, and severity of rotator cuff tears varies greatly, requiring equally diverse preoperative planning and surgical interventions. Video Atlas of Arthroscopic Rotator Cuff Repair by Uma Srikumaran and esteemed contributors provides a concise, well-rounded perspective on the surgical management of rotator cuff pathologies. Expert surgeons from across the globe describe and demonstrate numerous approaches, enabling clinicians to expand their armamentarium and achieve optimal outcomes. The opening chapters lay a solid foundation, covering basic techniques for arthroscopic repair of various rotator cuff tear patterns, patient positioning, portal placement, tips and tricks, complications, and pitfalls. Subsequent chapters succinctly discuss a comprehensive range of arthroscopic and transosseous techniques, biologic augmentation, grafting, tendon transfers, and superior capsular reconstruction"--